IDENTIFIKASI JENIS POHON PENGHASIL BUAH KONSUMSI DI KAWASAN HUTAN TEMBAWANG DUSUN SUAK DESA MANIS RAYA KECAMATAN SEPAUK KABUPATEN SINTANG - Paulina, Oktavianti; Manurung, Togar Fernando; Rifanjani, Slamet (Universitas Tanjungpura, 2020)
Identification is determining the identity of a species, which in this case determines the correct name and place in the classification. Tembawang Forest is a form of land management carried out by Dayak tribes in West Kalimantan. Tembawang Suak has various fruit trees species which are usually used by people around the forest. This research was conducted in Tembawang Forest at Suak Subvillage, Manis Raya Village, Sepauk District, Sintang Regency, West Kalimantan. The purpose of this study is to identify and describe the morphological characteristics of fruits trees species in the Tembawang Forest Area. The method in this research is an exploration method which is carried out by taking data with making pathways to facilitate roaming at the research location to find the fruit trees species and then taking a sample of the herbarium. Data analysis by describing morphological characteristics (generative and vegetative) in detail. Based on the research results, there are 30 species of consumption fruit trees that are classified into 16 genera and 13 families, and 5 species of which are endemic to Kalimantan, namely Manginfera pajang Kosterm (Asam Mawang), Shorea stenoptera Burck. (Tengkawang Tungkul), Durio kutejensis (Hassk.) Becc. (Pekawai), Sarcotheca macrophylla Blume (Rembai/Belimbing Hutan), and Baccaurea angulata Merr (Menit/Belimbing Darah).Keyword : Tree Identification, Fruit Producers, Tembawang Forest